IMPLICATION OF CONFLICT OF OWNERSHIP REGIONAL ASSETS IN THE EXPANSION OF BAU-BAU CITY IN THE TERRITORY OF EX BUTON SULTANATE - Darmin Tuwu (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
The article entitled